Utility of the Infantile Hemangioma Referral Score (IHReS) as a decision-making tool for referral to treatment - Leelawadee Techasatian; Kanokporn Chitpiromsak; Charoon Jetsrisuparb (BMJ Publishing Group, 2021)
Background The general paediatricians and primary care physicians sometimes face immense difficulty in referral judgements regarding which infantile hemangiomas (IHs) require referrals and when is the appropriate time to refer IHs for treatment. This resulted in the treatment being delayed beyond IHs' critical timeframe. The Infantile Hemangioma Referral Score (IHReS) has been recently developed, with the aim to solve this problem.Objectives The objective of the present study is to evaluate the reliability of IHReS and to assess the possibility of using this instrument in our country where a similar problem of delaying treatment of IHs is currently existing.Methods The present study was a prospective, cross-sectional study. Thirteen selected clinical cases were used to assess the reliability of IHReS among physicians who may have had the chance to deal with patients with IHs. The target physicians across the country were asked to participate in the study via an online platform (Google Forms) to decide whether to refer patients with IHs for treatment or observe. There were 3 steps of assessment: step 1, usual practice evaluation; step 2, using IHReS; step 3, retesting by using IHReS.Results Substantial agreement was observed after using IHReS (step 2) for interrater reliability, with Fleiss' Kappa values of 0.80 and 0.78 among IH experts and non-expert physicians, respectively. Regarding repeatability, in the test-retest assessments, Cohen's Kappa coefficient values revealed almost perfect agreement in intrarater repeatability for both experts and non-expert physicians (1.00).Conclusion IHReS is a simple, easy-to-assess tool for non-expert physicians. The benefit in the increase of interrater agreement was found in both IH experts and non-expert physicians. It has had the reliability to be used in making referral decisions regarding patients with IH for treatment among Thai physicians. Using IHReS can improve clinical outcomes by identifying which patient needs early intervention to minimise the possible complications.